Inquiry of Suicide Rates and their Liaison with Sociocultural and Socioeconomic Indicators in Spain - Vaquero-Diego, Maria; Orozco Valencia , Alexy; Ryan, Donal Nicholas (Transformations In Business & Economics, 2025)
In Spain, the suicide rate has been on the rise for the past few years. Research shows that people between the ages of 51 and 64 are at the greatest risk of an increased rate of suicide. The number of people committing suicide has also increased among older in recent years. The goal of this paper is an exploratory analysis of the relationship between four social dimensions and the suicide rates in different regions in Spain, without considering people diagnosed with psychological problems or mental disorders. Results showed some areas with the highest number of suicides.  Remarkable Canaries region presented huge suicide rates among its population, with suicide being among the upper incidence causes of death in the region. We can highlight slight associations between leisure/social relations and satisfaction with life with the number of suicides in men, which could be contrasted with differences between the autonomous states of Spain.
Keywords: suicide; human development; quality of life; public health; statistical methods